Vancomycin Loaded Glycerol Monooleate Liquid Crystalline Phases Modified with Surfactants - Spomenka Milak; Angela Chemelli; Otto Glatter; Andreas Zimmer (MDPI AG, 2020)
The influence of two tuning agents, polyglycerol ester (PE) and triblock copolymer (TC), on the properties of glycerol monooleate (MO) liquid crystalline phase (LCP) was investigated to achieve the therapeutic concentration of vancomycin hydrochloride (VHCl) into the eye, topically during 60 min (1 h) and intravitreally during 2880 min (48 h). Different techniques were used to elucidate the impact of surfactants on the structure of the LCP: polarized light microscopy (PLM), small-angle X-ray scattering (SAXS), and in vitro release tests I and II (simulating local and intravitreal application in the eye). The structure analysis by SAXS depicts that the inclusion of PE into the MO LCP provided partial transition of a hexagonal phase into a lamellar phase, and TC induced a partial transition of a hexagonal phase into an LCP which identification was difficult. The LCP modulated with PE and TC demonstrated different VHCl's release patterns and were evaluated by comparing our release data with the literature data. The comparison indicated that the LCP modulated with 30% w/w PE could be a promising VHCl delivery system intravitreally during 2880 min.